Factors Influencing Dietary Changes of Walleye Pollock, Gadus chalcogrammus, Inhabiting the East Sea off the Korean Coast - Joo-Myun Park; Hae-Kun Jung; Chung-Il Lee (Journal of Marine Science and Engineering, 2021)
This study examined the dietary patterns of walleye pollock, Gadus chalcogrammus, off the middle eastern coast of Korea between January 2016 and December 2017 to determine the influences of various predictors on dietary changes. Based on stomach content analyses, walleye pollock was found to be a demersal carnivore that mainly consumes carid shrimps, euphausiids, mysids, teleosts, and cephalopods. The main prey species identified in the diets of walleye pollock were Euphausia pacifica (euphausiids), Themisto japonicus (amphipods), Neomysis spp. (mysids), Neocrangon communis, Pandalus borealis (carid shrimps), Watasenia scintillans (cephalopods), and Bothrocara hollandi (teleosts), which are hyper-benthic and bentho-pelagic organisms. Dietary analyses based on the weight contributions of different prey taxa to the diets revealed significant variations in dietary composition in terms of fish size, water depth, and season, implying intraspecific dietary segregation. Euphausiids dominate the diets of smaller individuals (<30 cm TL), whereas the contributions of carid shrimps, teleosts, and cephalopods increase as body size increases. Similarly, the latter three prey items are dominant food resources in deeper habitats. The PERMANOVA results revealed that the size-related spatial and temporal changes in dietary composition are all significant for the species, as well as their two- or three-way interactions among those factors, except for the size-depth interaction. The coupling effect of size and depth is indicative of depth-dependent differences in fish sizes, with the tendency for larger individuals to be distributed in deeper habitats. In addition, seasonal and interannual variations in water column structures are also evident in the diets, which may, in part, account for the diet seasonality observed in the stomach content analysis. The dietary analyses of walleye pollock will improve our understandings to seek functional role of the species in benthic food webs, and to predict the effects of environmental and ...